Complementing and improving grazing systems for stocker and cow-calf production - Jones, Tatiana Marie (My University, 2025)
Grazing management strategies have given producers the ability to both improve rangeland and grazing lands, while also the potential to destroy quality and profitable grazing prairie through overgrazing, overstocking, understocking, and improper knowledge of natural flora and cattle grazing behaviors. Overgrazing often leads to the encroachment of noxious weeds. The Flint Hills of Kansas suffers from the increasing number of infested acres of Sericea lespedeza, an invasive plant. Although at one time it was used for soil erosion control and as a hay crop, wild S. lespedeza contains high levels of tannins, thus decreasing the palatability for grazing animals. Because complete eradication is unlikely, producers use a variety of methods to decrease encroachment and plant numbers. The goals of range management remain constant, regardless of geographical location or size of operation. Improvement of rangeland does not occur instantaneously, but with dedication, advancement will occur. Grazing management also incorporates an understanding of supplementation strategies to either improve animal performance, pasture performance, or a combination of both. Four studies were conducted to evaluate of several management options that can be used to improve pasture management for grazing cattle. Study 1: The objective was to utilize cattle to manage S. lespedeza in pastures. Pastures (n = 8) had four treatments applied that consisted of CON (no management), spraying high S. lespedeza infestation areas within pasture with a molasses spray at 12.5, 25, or 50% (v/v). Plant counts and animal grazing behavior were evaluated over a 92 d grazing period on tallgrass native range. Spraying S. lespedeza with molasses reduced the number of plants growing as compared to CON. Specifically, the 12.5% level had greater control than the 50% with 25% being in the middle. These results could be explained by steers spending more time in the areas immediately surrounding the 12.5% than any other treatment. Even though spraying S. lespedeza plants with molasses resulted in a lower number of plants at the end of the grazing period, this management option may not be practical for producers to implement. The cost for the molasses and labor made this more expensive than spraying techniques and burning. Additionally, molasses was damaging to spray equipment, thus needing replaced several times, which further increase cost. Study 2: the objective was to evaluate steer growth performance, pasture utilization, and ruminal fermentation characteristics (via in vitro procedures) of mineral supplements that contain either lasalocid, an ionophore (ION) or essential oils (EO), or both. Briefly, 281 steers were allowed to graze tallgrass native range for 92 d during the summer. Steer body weight gains, mineral intake, and forage intake were not different based on mineral supplemented to steers. Addition of minerals increased ruminal energetics and this was enhanced by addition of ION and EO and even further improved with the COMBO of ION and EO. Based on these results, there is potential for EO to replace the ION for cattle operations that are marketing animals in the natural and/or organic feeding programs. Study 3: Evaluation of corn silage supplementation on different varieties of fescue for cow-calf operations for cattle performance and forage utilization. Two years of data were collected on multiparous and primiparous Angus-cross beef cows (n = 45; Year 1 and n = 48; Year 2) grazing two varieties of fescue (TOX and NONTOX) in a 2 x 2 factorial arrangement where the second factor was supplementation (NOSUPP; no supplementation or SUPP; supplementing cows 1% of BW on DM basis of corn silage daily). Cow and calf growth performance were measured from mid-second trimester through weaning. Supplemented cows had greater weight gain through the entire supplementation period and had greater increase in BCS from 3rd trimester through lactation. Supplementation had no effect on calf birth weight or milk production. Supplementation tended to increase forage mass by 7.48% over NONSUPP pastures, while not impacting forage accumulation or quality. Weaning weight tended to be greater for NONTOX-SUPP as compared to TOX-SUPP and TOX-NONSUPP. Cows grazing TOX fescue had lower weight gains, more hair length, greater hair score, and lighter calf birth weights than NONTOX. TOX pastures had 12.27% greater forage mass with no differences in forage accumulation. Replacing toxic fescue with non-toxic varieties is a better option to improve productivity in cow herds than offsetting issues with supplementation. Supplementation may only have benefits during low forage years. Study 4: Evaluation of corn silage supplementation on bermudagrass pastures for cow-calf operations for cattle performance and forage utilization. Two years of data were collected on multiparous and primiparous Angus-cross beef cows (n = 24 each year) grazing bermudagrass pastures (n = 8; 3 cows per pasture) and received one of two supplementation treatments (NOSUPP; no supplementation or SUPP; supplementing cows 1% of BW on DM basis or corn silage daily). Each pasture contained a bred heifer (<2 years of age), 3-5 year old cow, and a 6+ year old cow. Cow and calf performance was measured from mid-second trimester through weaning. Supplementing had no effect on body weight, body condition score, hair length, nor hair score. Rump fat was increased with SUPP during the second trimester. Supplementation had no effect on calf birth weight and estimated milk output, but dams that were NONSUPP during gestation had greater dam adjusted 205 d weaning weight. First calf heifers had the lightest birthweight calves, lowest milk output, and lightest actual weaning weight while the OLD (>6 yr old) dams had the highest values and MID aged cows intermediate. Forage accumulation, forage mass, and forage nutrient quality were not impacted by supplementation methods. Offering corn silage to pregnant non-lactating cows grazing high quality bermudagrass could slightly improve cow condition but had no other economic benefits. Feeding 1% of corn silage daily was not a sufficient amount to result in more available forage.
Keywords: Grazing management; Invasive species; Tallgrass native range; Lasalocid; Cow-calf performance; Fescue toxicosis